2011
DOI: 10.1002/fut.20532
|View full text |Cite
|
Sign up to set email alerts
|

The information content of the S&P 500 index and VIX options on the dynamics of the S&P 500 index

Abstract: Given that both S&P 500 index and VIX options essentially contain information about the future dynamics of the S&P 500 index, in this study, we set out to empirically investigate the informational roles played by these two option markets with regard to the prediction of returns, volatility, and density in the S&P 500 index. Our results reveal that the information content implied from these two option markets is not identical. In addition to the information extracted from the S&P 500 index options, all of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 67 publications
4
32
0
1
Order By: Relevance
“…Wong and Tu (2009) conduct a study of information content of TVIX (Taiwan volatility index) and show that TVIX contains all the important information to predict the future realized volatility. Chung et al (2011) recently examine the information content of S&P 500 VIX options and describe that information content of implied volatility from two options markets is not same. In addition, they observe that the information extracted from S&P 500 index options and the information recovered from VIX options significantly improve all the prediction on the S&P 500 index.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wong and Tu (2009) conduct a study of information content of TVIX (Taiwan volatility index) and show that TVIX contains all the important information to predict the future realized volatility. Chung et al (2011) recently examine the information content of S&P 500 VIX options and describe that information content of implied volatility from two options markets is not same. In addition, they observe that the information extracted from S&P 500 index options and the information recovered from VIX options significantly improve all the prediction on the S&P 500 index.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Liu (2012) investigates the predictive power of TVIX implied volatility index in the Taiwan stock market, they show that implied volatility index also hold the predictive power to forecast the future market volatility like the implied volatility of call and put options and they conclude that TVIX is an effective indicator of future volatility in the emerging markets. The studies (Daigler and Rossi 2006;Konstantinidia et al 2008;Szado 2009;Chung et al 2011;Konstantinidi and Skiadopoulos 2011;Shu and Zhang 2012) have demonstrated the informational efficiency of implied volatility index and shown that volatility products (say VIX F&Os) are helpful in the price discovery and portfolio risk management.…”
Section: Introductionmentioning
confidence: 99%
“…Estimation using various data sources can produce distinct empirical results which show their different information content (see e.g. Bardgett et al (2013), Chung et al (2011)). In the framework of parameterized SDE model for VIX, employing VIX and its derivatives (futures and options) has been implemented before.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Variables one can think of are liquidity measures (Baker and Stein, 2004), VIX options (Chung, 2011), inflation, industrial production, the three-month T-bill rate, the 12-month treasury bond, the dividend yield and the price earnings ratio (See amongst others: Longin and Solnik, 1995, Pesaran and Timmerman, 1995, Campbell and Thompson, 2008. In this paper we design Lagrange Multiplier based tests that can determine whether adding explanatory variables to Hawkes models is beneficial.…”
Section: Introductionmentioning
confidence: 99%